The Properties of Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) and its Applications in Tissue Engineering - Yang, Qixiang; Wang, Jing; Zhang, Shu; Tang, Xiaoshan; Shang, Guangwei; Peng, Qiang; Wang, Raorao; Cai, Xiaoxiao (Current Stem Cell Research & Therapy, 2014)
Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) is a member of the polyhydroxyalkanoate (PHA) family. It is the designation of molecules consisting of random co-polymers of 3-hydroxybutyrate and 3- hydroxyhexanoate. PHBHHx plays a significant role in the field of biomedical materials. It has good physical, chemical and mechanical properties, making it potentially useful for a wide range of biomaterials applications. In addition, it has also shown better biocompatibility with different cell types. This paper will introduce the physical, chemical and biological properties of PHBHHx, including biodegradation, hydrophilicity, surface properties and cytocompatibility. The development of PHBHHx in tissue-engineering applications will be discussed. PHBHHx used to repair bone, cartilage, tendons, nerves and vessels will be the focus of discussion.
Keywords: osteoblast